Kloning dan Sekuensing Gen Xilanase dengan Produk Gen Berukuran 30 kDa dari Bacillus halodurans CM1 pada Escherichia coli DH5Î± - Safirah, Dearesty; Helianti, Is; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto (Bioma : Berkala Ilmiah Biologi, 2016)
The paper industry contributed the environment pollution due to chlor substances. Utilization of alkalothermophilic xylanase enzyme as a biocatalyst in the production of paper may become an environmentally friendly biobleaching alternative. Bacillus halodurans CM1 produces xilanase enzyme that had optimal activity at pH 9 and temperature 70Â°C. Previous study showed that this CM1 strains has several xilanase genes. The cloning of one of these alkalothermophiic xylanase (alkxyn) gene has been already conducted. This study aimed to clone alkxyn gene that encode alkalothermophilic xylanase enzyme from B. halodurans CM1 into Escherichia coli DH5Î±. Amplification of alkxyn has been carried out using primers for amplification xylanase 30 kDa. The alkxyn gene fragment was inserted into pGEM-T Easy vector and then transformed into E. coli DH5Î±. The results showed that the recombinant of E. coli DH5Î± harboring alkxyn gene from B. halodurans CM1 has been obtained. The sequences analysist based on BLAST showed that alkxyn fragment has homology (99%) with the alkaliphilic xylanase gene from Bacillus sp. 31 which encodes alkaliphilic xilanase (Genebank assession number: JF912895.1).Â Keywords: cloning, Bacillus halodurans CM1, xylanase, alkalothermophilic.